Reconstruction of Islamic Education Management through an Integral–Interconnected Approach in the Perspective of Visionary Leadership: A Systematic Literature Review - Sigit Apriyanto; Adelina Anum (CV. Creative Tugu Pena, 2025)
Islamic education management faces multidimensional challenges in the era of globalization, technological disruption, and increasing social complexity. The fragmentation of knowledge, the dominance of administrative approaches, and the weak integration of spiritual values with managerial practices constitute major obstacles to the development of Islamic educational institutions. This study aimed to reconstruct the paradigm of Islamic education management through an integral–interconnected approach within the perspective of visionary leadership using a Systematic Literature Review (SLR) method. The review examines scholarly articles and academic books published between 1993 and 2025, retrieved from the Google Scholar, DOAJ, and Garuda databases. The literature selection process followed the PRISMA flow, including identification, screening, eligibility, and inclusion stages. Data were analyzed through thematic coding and conceptual synthesis. The findings indicate that reconstructing Islamic education management requires epistemological integration between religious knowledge and modern science, the integration of managerial systems, and the strengthening of organizational culture grounded in tauhid values. Visionary leadership functions as a catalyst for transformation through the development of an integrative vision, alignment of organizational strategy, and continuous innovation. This study proposes a conceptual model for reconstructing Islamic education management based on an integral–interconnected framework that emphasizes the integration of values, systems, and transformational leadership.